Sixteen-Year Cohort of Liver Transplantation in the National Health System in Brazil: Analysis of Immunosuppression Maintenance Therapies - Nascimento, Guilherme Fagundes; Gomes, Rosângela Maria; Alvares-Teodoro, Juliana; Ribeiro, Nélio Gomes; Cherchiglia, Mariângela Leal; Simão-Filho, Charles; Acurcio, Francisco Assis; Sarmento, Tulio Tadeu Rocha; Gargano, Ludmila Peres; Guerra, Augusto Afonso (Frontiers in Pharmacology, 2020)
Objective: To evaluate factors related to liver graft survival with a focus on immunosuppressive schemes based on calcineurin inhibitors (tacrolimus or cyclosporine). Methodology: This study was carried out through an open cohort constructed by deterministic and probabilistic matching through three databases of the SUS with assessment of liver graft survival from 2000 to 2015 in Brazil. From this first cohort, a second cohort was constructed by pairing 1: 1 to more precisely assess the effect of the immunosuppressive scheme on graft survival. The Kaplan-Meier method and was used to estimate the probability of survival. Cox's model of proportional risks was used to assess factors related to graft loss. Result: We found 12,687 patients in the Full cohort and 470 patients in the Matched cohort. The overall graft survival rates at 1, 5, 10 and 16 years were 72.6%, 63.3%, 52.8% and 45.3%, respectively. Patients younger had a longer graft survival than older ones. In the Full cohort, male patients had a higher survival rate than female ones. Therapeutic schemes based on tacrolimus were more prevalent and had a better survival rate when compared to schemes that used cyclosporine. Tacrolimus without association with antiproliferative agents or rapamycin inhibitors was the therapeutic scheme associated with greater survival rate in both cohorts (HR = 0.81, 95% CI = 0.72-0.91), (HR = 0.50, 95% CI = 0.30-0.85). In addition, white-skinned patients had longer survival rate in both cohorts (HR = 0.55, 95% CI = 0.50-0.61), (HR = 0.50, 95% CI = 0.34 -0.75). On the other hand, patients who a greater time ratio without using an immunosuppressant had lower graft survival rate (HR = 6.46, 95% CI = 5.05-8.27), (HR = 6.57, 95% CI = 2.66 -16.22). Conclusion: This 16-year cohort showed that the older age and the greater time ratio without using an immunosuppressant are risk factors for liver graft loss. White-skinned patients and tacrolimus-based regimens, especially tacrolimus without other immunosuppressants, are factors of better prognosis to the graft.